Update of R&D findings and commercialisation [abstracts] - Malaysian Science and Technology Congress (1998 : Kota Kinabalu, Sabah); Malaysia. Kementerian Sains, Teknologi dan Alam Sekitar; Confederation of Scientific and Technological Associations in Malaysia (COSTAM) (Kota Kinabalu : MASTIC, 1998)
39